Exploring Green Consumer Behavior in Choosing Environmentally Friendly Products in Bandung City - Ian Zulfikar (SEAN Institute, 2025)
Sustainable consumption has become a critical issue as pressure on the environment increases due to modern consumption patterns. Green consumers are defined as individuals who consider environmental impacts in every purchasing decision, not only at the selection stage but also during product use and disposal. This study aims to explore the behavior of green consumers in selecting environmentally friendly products in Bandung City. This study used a qualitative method with a descriptive approach, where data was obtained through in-depth interviews and observations of consumers who had purchased environmentally friendly products, such as organic products, recycled packaging, and environmentally friendly household products. The results indicate that internal factors, such as personality, personal values, attitudes, and environmental awareness, play a significant role in influencing consumers' decisions to choose green products. Consumers with a high level of concern for health and the environment are more consistent in integrating environmentally friendly products into their daily lifestyles. Furthermore, external factors also play a role, including family support, peer influence, marketing campaigns, and the role of the community and media in shaping consumers' positive perceptions of green products. However, this study also identified several challenges, including relatively higher product prices, limited availability, a lack of transparent information, and skepticism about environmentally friendly claims due to the phenomenon of greenwashing. The conclusion of this study confirms that green consumer behavior in Bandung City is the result of an interaction between internal motivation and external influences. However, it requires more comprehensive educational, distribution, and policy support for broader and more sustainable development.